Electro-mechanical characterization of three-dimensionally conductive graphite/epoxy composites under tensile and shear loading. (October 2019) - Sherman, Riley; Chalivendra, Vijaya; Hall, Asha; Haile, Mulugeta; Nataraj, Latha; Coatney, Michael; Kim, Yong
Abstract: An experimental study was performed to compare the electro-mechanical response of three-dimensionally conductive woven carbon fiber/epoxy laminated composites under quasi-static uniaxial tensile and in-plane shear loading conditions. Three-dimensional (3D) electrical network was generated in these composites by embedding carbon nanotubes (CNTs) of 0.025 wt% in the epoxy and reinforcing short carbon fibers (150 μm and 350 μm long) with a fiber density of 1000 fibers/mm 2 between the laminates using electro-flocking process. CNTs are effectively dispersed in the epoxy matrix using a combination of ultrasonication and shear mixing techniques. A compression molding fabrication technique was employed to fabricate composite materials. For all composite types, in general, the in-situ electrical response showed a trend of initial decrease in resistance and later increase in resistance for tensile loading. However, no noticeable increase in electrical resistance was observed until failure of the composite under shear loading conditions. Both CNTs and short carbon fibers made new contacts with neighboring carbon fiber laminates for entire duration of shear loading even though the composite was undergoing progressive failure. Highlights: Fabricated novel three-dimensionally conductive graphite composites using carbon nanotubes and short carbon fibers. Electro-mechanical response of composites under tensile loading showed initial decrease and later increase in resistance. Electro-mechanical response of composites under shear loading showed only decreasing trend of resistance.